EDUCATIONAL APPLICATION TO KNOW NUMBER IN 5 LANGUAGES FOR KINDERGARTEN BASED ON ANDROID - Eko Sudaryanto; Febi Ayu Kurniawati (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2019)
Based on interviews with kindergarten teachers on number recognition subjects in severallanguages, there are still many students who experience difficulty in pronunciation and memorization.The purpose of this study is to help students learn to recognize symbols that are easy to understandand more fun. The system method used is the MDLC (Multimedia Development Life Cycle) version ofLuther - Sutopo. There are 6 (six) stages applied to this method, namely Concept, Design, MaterialCollecting, Assembly, Testing, Distribution. The software used by researchers in making thisapplication is Adobe Flash Professional CS6.  The results of beta testing using questionnaires on 7 respondents showed that 93.7% saideducational applications recognize numbers in 5 languages for toddlers based on Android inaccordance with the initial purpose of making educational applications to recognize numbers in 5 languages. Keywords: Application, Numbers, Android, MDLC ABSTRAK       Berdasarkan wawancara dengan guru  TK tentang mata pelajaranpengenalan angka dalambeberapa bahasa masih banyak siswa yang mengalamikesulitan dalam pengucapan danpenghafalannya. Tujuan penelitian ini untukmembantu siswa belajar mengenal lambang bilangan yangmudah dipahami danlebih menyenangkan. Metode sistem yang digunakan adalah MDLC(MultimediaDevelopment Life Cycle) versi Luther – Sutopo. Terdapat 6 (enam) tahapanyangditerapkan pada metode ini yaitu Pengonsepan, Perancangan, Material Pengumpulan Materi,Pembuatan, Pengujian, Pendistribusian. Software yang digunakan oleh penelitidalam pembuatanaplikasi ini adalah Adobe Flash Professional CS6.  Hasil dari pengujian beta testing menggunakan kuisioner pada 7 responden menunjukanbahwa93,7% mengatakan aplikasi edukasi mengenal angka dalam 5 bahasa untuk anakbalita berbasisandroid sesuai dengan tujuan awal pembuatan aplikasi edukasimengenal angka dalam 5 bahasa. Kata Kunci : Aplikasi, Bilangan, Android, MDLC